Medium formulation and impeller design on the biosynthesis of high molecular weight hyaluronic acid by Streptococcus zooepidemicus ATCC 39920 - Lai, Zee Wei; Abdul Rahim, Raha; Ariff, Arbakariya; Mohamad, Rosfarizan (Academic Journals, 2011)
The effects of medium formulation and impeller design (Rushton turbine and helical ribbon) on hyaluronic acid (HA) biosynthesis by Streptococcus zooepidemicus ATCC 39920 were investigated using a 2 L stirred-tank bioreactor. The effect of different glucose concentrations (20, 30, 50 and 60 g/L), nitrogen sources ((NH4)2S2O8, (NH4)2PO4, yeast extract, and tryptone) and carbon/nitrogen ratios on the growth of the strain and on HA biosynthesis were initially investigated. Organic nitrogen sources (yeast extract and tryptone) were proven to be favourable in media for HA biosynthesis compared to inorganic nitrogen sources. About 2.442 g/L of HA with a high molecular weight (4.36 x 106Da) was synthesised at an optimal C/N of 2.5:1 (using a mixture of yeast extract and tryptone) in a 2 L stirred-tank bioreactor equipped with a Rushton turbine impeller. When using an optimal medium formulation at equal HA production levels, the helical ribbon impeller resulted in a higher molecular weight of HA (5.20 x 106 Da) compared to the Rushton turbine impeller.